IKON, INDEKS, DAN SIMBOL DALAM PROMOSI WISATA DI SULAWESI SELATAN:PERSPEKTIF SEMIOTIKA KOMUNIKASI CARLES SANDERS PEIRCE - Ismail, Risdayanti; Mahmudah, Mahmudah; Faisal, Faisal (Fakultas Bahasa dan Sastra Indoensia, 2024)
This research aims to analyze icons, indices and symbols in tourism promotion in South Sulawesi using Charles Sanders Peirce's perspective of communication semiotic theory. The data comes from the South Sulawesi TVC video uploaded by the South Sulawesi Culture and Tourism Service on its official Instagram account, namely @budparsulsel. The focus in this research is the object referred to by the sign in creating visual communication. This type of research is descriptive qualitative research to describe the icons, indices and symbols contained in promotional videos. The research results show that tourism promotional videos in South Sulawesi are formed through visual signs, icons, indices and symbols chosen to represent tourist attractions in South Sulawesi. This sign not only displays natural charm, but also the values of tolerance, spirituality, culture and also the character of the people of South Sulawesi.